The Role of Interactive Multimedia Teaching Tools for Enhancing Academic Achievement: A Case Study of the Provincial Studies Course, Yala Community College - Phongsuwarisi, Wanphen (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This research was the experimental research in one group to before and after and the objectives were to: on learning achievement and to examine students’ satisfaction toward their use in the Provincial Studies course at Yala Community College. The sample group was 40 students enrolled in the GE 0201 Provincial Studies course during the first semester of the 2024 academic year and selected using simple random sampling. The research instruments included: (1) interactive multimedia worksheets designed by the researcher using the LIVEWORKSHEETS platform, which allows for interactive learning aligned with the principles of multimedia learning theory and cognitive load theory; and (2) a learning achievement test, consisting of 20 multiple-choice questions to assess foundational knowledge and three short-answer questions to evaluate analytical and integrative thinking. Data were analyzed using descriptive statistics and paired t-tests. The findings revealed that: 1) students’ posttest scores (M = 5.04, S.D. = 0.36) were significantly higher than their pretest scores (M = 3.45, S.D. = 0.36), with statistical significance at the 0.05 level (t(39) = 38.74, p<.001); and 2) students reported high satisfaction with the use of the interactive multimedia worksheets overall (M = 3.75, S.D. = 0.75), particularly noting that the worksheets enhanced their understanding of the course content (M = 4.41, S.D. = 0.58). These results indicate that the interactive multimedia worksheets effectively facilitated students’ learning and comprehension of the Provincial Studies course. Future research should explore comparisons between experimental and control groups and analyze the impact of specific multimedia components on learning outcomes.